A Study on The Knowledge of Tetanus Immunization Among Internees in A Government Medical College of Kolkata - Ranadip Chowdhury; Abhijit Mukherjee; Saibendu Kr Lahiri (Medsci Publications, 2011)
The current study was undertaken to assess the knowledge of the internees regarding tetanus immunization in children, pregnant women and adults as per the NIS and the guidelines regarding tetanus immunization in relation to the wound categories depending on the immunisation status of the patients. A pre tested questioner used to access knowledge among 108 internees. 57.4% internees were not aware of the number of doses of tetanus vaccine recommended for children under the age of 16 years and 76.8% internees were not aware of the number of doses of tetanus vaccine recommended for adults over the age of 16 years. More than 90% of the internees considered contaminated wounds, animal bites, burn injuries and wounds greater than 6 hours old to be tetanus prone. 91.7% of internees had considered wounds greater than 6hours old as tetanus prone and 5.6% did not consider this wound to be tetanus prone. On the other hand, 97.2% of internees had considered contaminated wounds and animal bite to be tetanus prone and 2.8% did not consider. While 93.5% of internees considered burn injuries to be prone to the development of tetanus, 6.5% of internees thought otherwise.   13% of the internees did not consider human bite to be tetanus prone. 25% of the internees considered every cut injury to be tetanus prone. Better TT awareness of tetanus prophylaxis recommendations is necessary and tetanus prophylaxis recommendations may be more effective if they are better adhered to at the ED and the other departments that are involved in providing tetanus prophylaxis to their patients.